2002
DOI: 10.1086/341566
|View full text |Cite
|
Sign up to set email alerts
|

Innate and Acquired Resistance to Amebiasis in Bangladeshi Children

Abstract: Entamoeba histolytica infection and colitis occurred in 55% and 4%, respectively, of a cohort of Bangladeshi preschool children observed for 2 years. DNA typing demonstrated that infecting E. histolytica isolates were genetically diverse. Innate resistance to infection in children was linked to the absence of serum anti-trophozoite IgG. Most children who lacked serum anti-trophozoite IgG failed to develop it in response to a new infection. The serum anti-trophozoite IgG response clustered in families, which is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
129
2
2

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 144 publications
(143 citation statements)
references
References 36 publications
6
129
2
2
Order By: Relevance
“…A higher lectin-specific IgG level was found in ALA and intestinal amebiasis patients as compared with asymptomatic controls (61). In our study, we observed an increased frequency of new E. histolytica infections in children with serum IgG antibodies to the lectin (64). These findings suggested that systemic anti-lectin antibody response might not offer direct protection from amebiasis.…”
Section: Humoral Immune Response To E Histolyticacontrasting
confidence: 44%
“…A higher lectin-specific IgG level was found in ALA and intestinal amebiasis patients as compared with asymptomatic controls (61). In our study, we observed an increased frequency of new E. histolytica infections in children with serum IgG antibodies to the lectin (64). These findings suggested that systemic anti-lectin antibody response might not offer direct protection from amebiasis.…”
Section: Humoral Immune Response To E Histolyticacontrasting
confidence: 44%
“…In addition to invasive disease, the parasite asymptomatically colonizes the intestine of up to 11% of endemic populations (2,3). The mechanisms of human resistance to colonization or invasive disease are poorly understood.…”
Section: Resistance Of C57bl/6 Mice To Amoebiasis Is Mediated By Nonhmentioning
confidence: 99%
“…The mechanisms of human resistance to colonization or invasive disease are poorly understood. One contributing factor is fecal IgA to the parasite, particularly to its galactose-inhibitable adherence lectin, which correlates with partial protection against infection in children and vaccinated mice (3,4). Additionally, a protective role for IFN-␥, TNF-␣, and NO on macrophages has been demonstrated in vitro (5).…”
Section: Resistance Of C57bl/6 Mice To Amoebiasis Is Mediated By Nonhmentioning
confidence: 99%
See 1 more Smart Citation
“…3 Various studies from rural areas of Central and South America, India, and the tropical areas of Asia and Africa have reported prevalence rate as high as 55%. 4,5 Pyogenic liver abscess has an estimated global incidence of 1.1-2.3 per 100,000 person-years and in United States, the incidence is approximately 3.6 per 100,000 and has been rising. 6 Broadly divided into amoebic liver abscess (ALA) and pyogenic liver abscess (PLA) with majority of amoebic etiology in developing countries and pyogenic in developed countries.…”
Section: Introductionmentioning
confidence: 99%